Paracoccidioides: perfil proteômico após exposição à argentilactona, avaliação da inibição por argentilactona sobre isocitrato liase e padronização do método de micro-ensaio para as enzimas do ciclo do glioxilato - Prado, Renata Silva do (2014)
Dimorphic fungi of the genus Paracoccidioides spp. are etiologic agent of paracoccidioidomycosis (PCM), a human systemic mycosis with high incidence in Brazil. Due to the toxicity of existing drugs, the long treatment and resistant isolates, the search for new therapies has become relevant. In this study, we verified the activity argentilactone, extracted the essential oil of Hyptis ovalifolia and its derivatives against Paracoccidioides. The results showed a dose- dependent inhibition of argentilactone fungus in yeast cells, as well as during dimorphism. Inhibition of cell growth was higher than in the presence of acetate than glucose. Argentilactone also been shown to inhibit the native enzyme isocitrate lyase Paracoccidioides (PbICL) and recombinant (PbICLr). The greatest inhibition was observed in the presence of acetate, a condition in which the enzyme is demonstrably more active than glucose. In silico analysis showed that argentilactone binds to the catalytic site of PbICL. The micro-assays for PbICLr and malate synthase (PbMLSr) were standardized, allowing the search for inhibiting compounds on a large scale. A global analysis of Paracoccidioides proteomic profile in response to argentilactone allowed visualization of metabolic adaptation of the fungus to the compound. Important metabolic pathways were suppressed explaining the strong action of the compound on fungal growth and viability. In this study, alternative metabolic pathways adopted by the fungus were elucidated resulting in a better understanding of the mode of action of the compound. It was also evaluated the cytotoxicity and DNA damage caused by argentilactone in human cells, MRC5 and A549, concluding that it occurs in a dose-dependent manner. Thus, it is concluded that argentilactone is a candidate prototype antifungal for the treatment of PCM.